Teaching a Large Multi-Level Class Using Different Strategies and Activities to Motivate English Language Learning - Julia Sevy (Studies in English Language and Education, 2016)
Many challenges face English language teachers today, but two common problems in Ecuador specifically in universities are large class sizes and multi-level students. These problems can create boredom, anxiety, and over all lack of interest in English language learning. It is shown in this article how to combat these particular problems through various strategies utilized to teach to the students’ needs, help them work together and intrinsically motivate them to learn different English language skills, specifically grammar and sentence structure. These strategies include group work, task-based learning, the inverted or flipped classroom, role-play and intrinsic learning. The author explains how these strategies work in a specific group of university pupils in Ecuador to overcome these specific problems in a classroom, but without student participation they can be flawed.